Determinants of bone mineral density in various regions of the skeleton among smokers and non-smokers: the role of physical activity - Kopiczko, Anna; Czapla, Michał; Kubielas, Grzegorz; Uchmanowicz, Bartosz (Frontiers in Physiology, 2024)
The adult human skeleton is composed of cortical and cancellous bone. The proportions of these two types of bone tissue differ in various parts of the skeleton. The aim of this cross-sectional study was to quantify the determinants of bone mineral density (BMD) and bone mass content in various regions of interest (ROIs) in smokers and never-smokers.In this study, 4332 bone scans divided from 3 regions of interest (ROIs) were analyzed: the forearm (distal and proximal), femur and lumbar spine. Body composition and bone parameters were measured using dual-energy X-ray absorptiometry. Smoking was measured by the Global Adult Tobacco Survey questionnaire. Body mass index (BMI) was calculated and physical activity (PA) was characterized by metabolic equivalent of task (MET).Results Among women, the interaction between PA (positive β coefficient) and smoking (negative β coefficient) was a significant predictor of BMD in the distal and proximal forearm (adj. R²=0.40 and R²=0.58; p<0.001). The interaction of three variablesage, smoking (negative β), and MET (positive β) -was significant for total hip BMD (adj. R²=0.54; p<0.001).The interaction between BMI and MET (positive β) and smoking (negative β) was significant for BMD in the lumbar spine (adj. R²=0.62; p<0.001). In men, the interaction between MET (positive β) and smoking (negative β) was significant for BMD in the forearm and lumbar spine (adj. R²=0.44, R²=0.46, R²=0.49; p<0.01). Smoking alone was a significant negative predictor of total hip BMD (adj. R²=0.34; p<0.001).Among both women and men, never-smokers had significantly better bone parameters compared to smokers. Smoking was a significant negative predictor for BMD in the various ROIs in both women and men. Physical activity was a significant positive predictor of BMD, with a strong association with bone parameters.